Geochemical elements from DH-7B sediment core from the Dahu Lake, Ilan Plain - Abdur Rahman; Liang-Chi Wang; Kaoru Kashima; Hong-Chun Li; Huei-Fen Chen; Tien-Nan Yang (PANGAEA, 2025)
A 35-meter-long sediment core (DH-7B) was retrieved from Dahu Lake using a stainless-steel pipe mounted on a floating platform. The core was subsampled at 5-cm intervals with 1-cm thickness for diatom, stable isotope, and trace element analyses. For trace element analysis, dry sediment samples (0.5?g) were collected at 2-cm intervals and leached with 10?mL of 0.5N HCl. The resulting supernatant was analyzed for Ca, Mg, Sr, Ba, K, Na, Li, Fe, Mn, Al, Zn, and Cu using inductively coupled plasma optical emission spectrometry (ICP-OES)., and Pb.
In: Rahman, A et al. (2025): Typhoon and climate history of northeastern Taiwan during mid to late Holocene: inferred through the Dahu Lake sediment core, Ilan Plain [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.982469